Agresivitas Pajak di Sektor Tambang: Analisis Komparatif Indonesia - Australia - Siti Annisa; Anissa Yuniar Larasati (Universitas Batanghari Jambi, 2026)
This study aims to analyze the effect of profitability, liquidity, and company size on tax aggressiveness in coal mining companies listed on the Indonesia Stock Exchange (IDX) and the Australian Securities Exchange (ASX) during the period 2019–2023. The method used is a quantitative approach with multiple linear regression analysis techniques, based on 40 observational data from eight companies selected through purposive sampling. The results of the study indicate that simultaneously, the variables of profitability, company size and liquidity have a significant influence on tax aggressiveness, but partially only the liquidity variable has no influence on tax aggressiveness, while the variable of company size has a significant positive influence inversely proportional to profitability which has a significant negative influence on tax aggressiveness in coal mining companies listed on the Indonesia Stock Exchange (IDX) and the Australian Securities Exchange (ASX) during the period 2019–2023. These findings indicate that the internal financial characteristics of companies have an important role in shaping tax planning strategies, especially in strategic sectors such as mining.